What Orthopaedic Surgeons Need to Know: The Basic Science Behind Opioids. Issue 18 (15th September 2019) - Hagedorn, John C.; Danilevich, Maxim; Gary, Joshua L.
Abstract : On October 26, 2017, US president, Donald J. Trump, declared the opioid epidemic a national public health emergency. This declaration opened the door to government funding for programs geared toward studying and treating opioid addiction; however, part of the responsibility to slow the epidemic falls on physicians. Orthopaedic surgeons prescribed the third-highest number of narcotic prescriptions among all physician groups, and therefore, they have a major role to play in decreasing the use of opioids. Although restricting prescriptions is part of the solution, orthopaedic surgeries are often painful, and opioid medications, along with other multimodal nonopioid medications, allow patients to control pain and improve function, especially in the short term. Therefore, to successfully manage pain and opioid prescriptions, orthopaedic surgeons should know the basic science behind these powerful medications. Understanding the basic mechanism of action of opioid and nonopioid medication classes, knowing what oral morphine equivalent are, and knowing which nonopioid drugs can amplify or weaken the potency of opioids will help orthopaedic surgeons become more informed prescribers and leaders in helping control the opioid epidemic.